Research on the hypoglycemic effects of Desugan liquid extract on experimental animals - Nguyen, Thi Minh Thu; Trinh, Thi Ha; Tran, Van Thanh; Bui, Quang Tinh (Tạp chí Y Dược cổ truyền Việt Nam, 2025)
Objective: To test the hypoglycemic effects of Desugan liquid extract in experiments. Subjects and methods: The hypoglycemic effects of Desugan were evaluated in two experimental models including rats given 10.5 g/kg glucose orally and mice induced with type 1 diabetes by intraperitoneal injection of STZ at a dose of 100 mg/kg/day x 8 days. Results: After 14 days of Desugan oral administration at doses of 3.15 and 9.45 g/kg/day, rats’ blood glucose levels were significantly lower than those in the control group (p < 0.001) with the reduction rates after 1, 2, and 4 hours of glucose administration being 28.11%, 28.76%, and 23.22% (group 3) and 32.96%, 31.81%, and 25.42% (group 4), respectively. Furthermore, with similar oral administration intervals, Desugan at doses of 5.4 and 16.2 g/kg/day remarkablly reduced blood glucose levels in mice compared with that of the control group (p < 0.001) with respective reduction rates after 2 and 4 hours of sample administration being 40.38 and 51.26% (group 3) and 53.32 and 52.65% (group 4). Conclusion: Desugan had high effectiveness in reducing blood glucose levels in rats (given oral glucose) at doses of 5.15 and 9.45 g/kg/day × 14 days and in STZ-induced type 1 diabetic miceat doses of 5.4 and 16.2 g/kg/day × 14 days.